The role of the plasmid content in multiple resistance to antibiotics Life in isolated Rthomh of cases of diarrhea in children - Baghdad Science Journal (مجلة بغداد للعلوم, 2006)
Was conducted neutralize content Albulamedi for local isolates using Alacardan dye orange selection experience showed loss of local isolates resistant life antibiotic ampicillin, chloramphenicol